The fucosylation inhibitor, 2-fluorofucose, inhibits vaso-occlusion, leukocyte-endothelium interactions and NF-ĸB activation in transgenic sickle mice. - John D Belcher; Chunsheng Chen; Julia Nguyen; Fuad Abdulla; Phong Nguyen; Minh Nguyen; Nicole M Okeley; Dennis R Benjamin; Peter D Senter; Gregory M Vercellotti (PLoS ONE)
2-Fluorofucose (2FF) blocks the fucosylation and the tethering of sialyl-Lewisx tetrasaccharide and structural variants on leukocytes and red blood cells to P- and E-selectins on activated endothelial cell surfaces. Because P- and E-selectin are required for vaso-occlusion in murine sickle cell disease (SCD), we investigated whether 2FF would inhibit vaso-occlusion in SCD mice. Microvascular stasis was measured in subcutaneous venules in NY1DD and HbSS-Townes SCD mice with dorsal skin-fold chambers after infusion of hemoglobin or exposure to hypoxia/reoxygenation. 2FF in drinking water or administered by gavage inhibited stasis in sickle mice in a dose-responsive manner. Significant inhibitory effects on stasis were seen 1 day post-treatment. 2FF treatment of SCD mice also significantly reduced leukocyte rolling and adhesion along the vessel walls of SCD mice and the static adhesion of neutrophils and sickle red blood cells isolated from 2FF-treated SCD mice to resting and activated endothelial cells. Total white blood cell counts increased in response to 2FF. NF-ĸB activation and VCAM-1 and E-selectin expression were inhibited in the livers of SCD mice consistent with an overall decrease in vascular inflammation and ischemia-reperfusion physiology. Pretreatment with 2FF completely eliminated heme-induced lethality in HbSS-Townes mice, consistent with the observed anti-inflammatory and anti-adhesive properties of 2FF in SCD mice. These data suggest that 2FF may be beneficial for preventing or treating vaso-occlusive crises in SCD patients.